Prevalence of malnutrition and its related factors among urban and rural primary school students, Abadan, in 2019 - Saeedeh Elhami; Nasim Hatefimoadab; Farshid Mohammad Mousaei; Samaneh Naeimi; Maryam Azizi; Daniyal Sayadi Moghadam; Marzieh Ghassemi (Wolters Kluwer Medknow Publications, 2022)
Introduction: Malnutrition is one of the most important public health problems worldwide and has adverse effects on the physical as well as mental capacities of individuals, especially school-age children. This descriptive-analytical study aimed to investigate the nutritional status of primary-school students in urban and rural areas of Abadan. Methods: Multi-stage stratified-cluster and simple random sampling was performed on urban and rural primary school students in Abadan with the demographic information, height, and weight of 1133 students measured. Furthermore, the indices of short stature for age (stunting), low weight for age (underweight), and low weight for height (wasting) in children were calculated and compared with the National Center for Health Statistics standard. Results: The results revealed that the average age of malnourished children was 9.56 years and the average age of normal children was 8.97 years. The malnutrition prevalence among primary school children of Abadan was 8%, and there was a poor correlation between factors such as sex (P = 0/8), place of residence (P = 0/4), plus school place (P = 0/9), and malnutrition, while there was a positive relationship between with the parents' level of education and malnutrition (P = 0/02). Thus, the most influential factor seems to be the parents' level of education and awareness. Conclusion: Steps can be taken to promote the social and cultural level of families and prevent malnutrition as well as improve the nutritional status of society through collaboration among various institutions, holding educational classes with the presence of education departments, and encouraging families. The household economic status is also one of the important factors in the implementation of these educational classes that must be considered.